Wireless Power/Data Transfer, Energy Harvesting System Design - Lee, Byunghun (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book focuses on emerging wireless power/data and energy harvesting technologies, and highlights their fundamental requirements, followed by recent advancements. It provides a various technical overview and analysis of key techniques for wireless power/data and energy harvesting system design. The state-of-the-art system introduced in this book will benefit designers looking to develop wireless power transfer and energy harvesting technologies in a variety of fields, such as wearable, implantable devices, home appliances, and electric vehicles.